Energy justice in Japan's energy transition: pillars of just 2050 carbon neutrality. (21st April 2022) - Sokołowski, Maciej M; Kurokawa, Satoshi
Abstract: Energy justice is a topic that is currently being explored by energy law experts around the world and used across several academic fields in energy research. However, we note that this concept is quite novel in Japan (there have been no substantial publications published in either English or Japanese) and could be expanded. This is especially important in light of Japan's aspirations to achieve carbon neutrality by 2050 and implement a just energy transition. In this context, the article's goal is to present the energy justice theory in a legal (energy law) and policy (climate-energy policy) framework in Japan. The article discusses the five basic types of justice, referring to Japanese energy legislation and climate-energy policy as examples. The analysis includes an assessment of the carbon neutrality pillars (seen through the prism of energy justice theory), aimed at supporting Japan in meeting its climate targets, and directions related to the use of renewable, conventional and nuclear energy sources requiring examination in terms of energy justice (due to failures of energy policy, such as lack of stakeholder recognition, local conflicts, NIMBY, etc.). Furthermore, the article demonstrates the improvements required in the legal and policy frameworks in Japan to make the application of human rights and the Sustainable Development Goals across the energy life-cycle effective. This will also include an examination of potential legal and organisational changes, and new structures and appointments in the Japanese administration.